Building Smart Tourism: Exploring the Potential of Tourism Apps for Branding - Serlina, Andi; Lutfi, Muhammad; Baharuddin, Baharuddin (Department of Government Studies, Universitas Muhammadiyah Buton., 2024)
This research comprehensively studies the impact of the